Mastering exposure in digital photography learn by video - Grey, Tim (Peachpit Press, 2011)
"This innovative product uses interactive video to explain how to manage camera exposure, a topic many photographers don't fully understand. Exposure settings have tremendous impact on the overall brightness and contrast of an image and ultimately its quality. Viewers will learn how to optimize exposure and maximize detail, minimize noise, and create the best images possible. This workshop begins with an overview of key exposure concepts, then discusses various exposure modes and some advanced concepts and techniques to help viewers master the concepts and practice of photographic exposure. It also covers some post-processing techniques related to exposure and includes some real-world examples that review core exposure concepts. Experienced instructor Tim Grey presents more than 3 hours of exceptional quality video tutorials, complete with lesson files, assessment quizzes, and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. The unique Watch-and-Work mode shrinks the video into a small window to allow the student to work alongside the instructor. Project files used in the lessons are included on the disc so viewers can practice what they've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.
Title and publication information from resource description page (viewed Aug. 25, 2011)
Keywords: Photography -- Exposure; Photography -- Digital techniques; Image processing -- Digital techniques; Digital cameras; Photographie; Exposition; Photographie numérique; Traitement d'images; Techniques numériques; Appareils photographiques numériques; digital imaging; Image processing; Digital techniques; Photography; Digital techniques; Photography; Exposure